The Phenomenon of a Mixed Colony: the Case of Lasius brunneus and Lasius umbratus (Hymenoptera, Formicidae) - Stukalyuk, S.; Radchenko , Yu.; Akhmedov, A.; Stelia, V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The aim of this work is to study to find out why, in the case of temporary social parasitism, a mixed colony of Lasius brunneus (Latreille, 1798) and Lasius umbratus (Nylander, 1846) exists in this state for many years. In 2023, a mixed colony of L. brunneus (host species) / L. umbratus (temporary social parasite) was discovered in Moldova. This mixed colony is located at the same site where another mixed colony containing Lasius fuliginosus (Latreille, 1798), L. umbratus disappeared in 2017. Video recordings of the intensity of movement of workers of the two species along the trails were made to study the frequency of antennal contacts and to calculate the colony population. Based on the previously used algorithms, it was assumed that the queen oviposition rate of L. umbratus is 1.5 times higher than that of L. niger, while that of L. brunneus is comparable to that of Lasius niger (Linnaeus, 1758). Chi-square test and post-hoc Dunn's test were used for statistical analysis of the data. Mathematical modelling was used to analyse the rate of colony development. Results of the analysis of worker activity on the trail showed that L. brunneus had 11 times more foragers than L. umbratus. A high number of interspecific antennal contacts between workers was recorded. The population of the mixed colony was estimated to be 48.880 L. brunneus and 24.433 L. umbratus workers. Mathematical modelling confirmed the failure of L. brunneus monogyny in a mixed colony and suggested that high L. brunneus abundance is ensured by multiple queens (oligogyny). Probably in 2021, the L. brunneus colony moved to a new habitat, which was invaded by the L. umbratus queen. After the invasion, several L. brunneus queens survived, allowing a mixed colony to exist.